2011
DOI: 10.1007/s11999-010-1623-y
|View full text |Cite
|
Sign up to set email alerts
|

Does Acetabular Inclination Angle Affect Survivorship of Alumina-ceramic Articulations?

Abstract: Background Reports in the literature have linked high acetabular inclination angles to increased wear of ceramicon-ceramic bearings. However, many of these studies were only conducted in vitro and did not address the clinical relevance of such findings. Questions/purposes We therefore determined: (1) whether the cup inclination angle influences survival or function in patients with ceramic-on-ceramic implants; (2) the incidence of radiolucencies, osteolysis, and subsidence of ceramic-on-ceramic implants; and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…In the Australian Orthopaedic Association National Joint Replacement Registry (AOA NJRR), the cumulative incidence of revision of CoC THA, with OA as diagnosis, at 10 years was 5.3%, which is similar to our findings after 8.7 years of follow-up. In studies with smaller series, a 5-year survival of 98% ( Johansson et al 2011 ) and a 6.7-year survival of 94–98% ( Garcia-Rey et al 2009 ) were found, corresponding to our findings. The main cause of revision in both studies was aseptic loosening.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the Australian Orthopaedic Association National Joint Replacement Registry (AOA NJRR), the cumulative incidence of revision of CoC THA, with OA as diagnosis, at 10 years was 5.3%, which is similar to our findings after 8.7 years of follow-up. In studies with smaller series, a 5-year survival of 98% ( Johansson et al 2011 ) and a 6.7-year survival of 94–98% ( Garcia-Rey et al 2009 ) were found, corresponding to our findings. The main cause of revision in both studies was aseptic loosening.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, simulator studies have shown less wear with CoC bearings, which—together with more bio-inert debris than polyethylene wear debris ( Christel 1992 )—may reduce the risk of aseptic loosening in CoC THAs, although this has not yet been shown in any study and should only become apparent with longer follow-up time. In the present study and in the above-mentioned studies with short- to medium-term follow-up ( Garcia-Rey et al 2009 , Johansson et al 2011 , Khatod et al 2014 ), revision due to aseptic loosening could certainly be related to fixation of the components rather than to wear.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The effect of cup orientation on bearing surface wear of hard bearings has been extensively investigated. Although most clinical retrieval and simulator studies identified increased bearing surface wear for high inclination,5, 12–14 some did not 16, 31. Similarly, controversy exists regarding acetabular anteversion effects; both increased15, 16 and decreased11 wear have been measured.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mesh zoning resolution, which was determined from mesh sensitivity convergence studies, was approximately equal for the entire contact region (shown here as the outlined elements near the edge of the cup). The edge loading challenge investigated was a trunk leaning maneuver, such as when tying shoes 67 .The motion and loading inputs were determined from kinematic and inverse dynamic data from human-subject optoelectronic motion capture 56 , some have not 224,232 . Similarly, controversy exists regarding acetabular anteversion effects, with both increased 212,224 and decreased 222 wear having been measured.…”
Section: Role Of Acetabular Geometry In Edge-loading 220mentioning
confidence: 99%